2011
DOI: 10.1073/pnas.1100682108
|View full text |Cite
|
Sign up to set email alerts
|

Methane contamination of drinking water accompanying gas-well drilling and hydraulic fracturing

Abstract: Directional drilling and hydraulic-fracturing technologies are dramatically increasing natural-gas extraction. In aquifers overlying the Marcellus and Utica shale formations of northeastern Pennsylvania and upstate New York, we document systematic evidence for methane contamination of drinking water associated with shalegas extraction. In active gas-extraction areas (one or more gas wells within 1 km), average and maximum methane concentrations in drinking-water wells increased with proximity to the nearest ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
825
4
17

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,099 publications
(880 citation statements)
references
References 17 publications
6
825
4
17
Order By: Relevance
“…Public concerns have been expressed about drinking-water contamination from migration of chemicals used during the hydraulic fracturing process, as well as from the escape of methane from fractured rock and well casings (Dammel et al, 2011;Groat and Grimshaw, 2012;Osborn et al, 2011;Rozell and Reaven, 2012;U.S. EPA, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Public concerns have been expressed about drinking-water contamination from migration of chemicals used during the hydraulic fracturing process, as well as from the escape of methane from fractured rock and well casings (Dammel et al, 2011;Groat and Grimshaw, 2012;Osborn et al, 2011;Rozell and Reaven, 2012;U.S. EPA, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, strong scientific evidence to support these concerns is lacking. To our knowledge, only one study has been published in the scientific literature evaluating the potential for groundwater contamination with methane (Osborn et al, 2011). These authors reported methane contamination of aquifers overlying the Marcellus Shale formation and noted that the contamination accompanied gas-well drilling and hydraulic fracturing activities in the area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts with the little information on hydrochemical aspects associated with the potential methane leakage during such an operation. Some papers deal with the stable isotopes of carbon, hydrogen and helium, which are meant to distinguish between man-made sources and natural occurrences (Taylor et al 2000;Breen et al 2007;Osborn and McIntosh 2010;Osborn et al 2011;Stuart 2012;Jackson et al 2013;Molofsky et al 2013;McMahon et al 2013). There are reports on elevated concentrations of arsenic, selenium and strontium in groundwater near fracking sites in the Barnett Shale formation of north Texas but it is not known whether the contaminants have a near-surface origin or are derived from a deep source (Fontenot et al 2013).…”
Section: Introductionmentioning
confidence: 99%